COVID-19 in Nigeria: Is the pharmaceutical sector spared? (2020)
The coronavirus disease 2019 (COVID-19) is an infectious disease caused by the newly discovered Severe Acute Respiratory Syndrome Coronavirus 2. The World Health Organization declared the novel coronavirus outbreak as pandemic after it was previously referred to as a public health emergency of international concern [1]. The first case of the disease in Nigeria was reported by the Federal Ministry of Health on the February 27, 2020 in Lagos. Since this period, there has been a steady geometric rise in the number of daily reported cases in the country with over 58,000 confirmed cases and 1100 deaths as of September 25, 2020. Many sectors have been impacted by the pandemic and the pharmaceutical sector is not an exception. This letter emphasizes how COVID-19 pandemic has impacted industrial, community and hospital pharmacy practice in Nigeria. The emergence of this pandemic brought with it, unprecedented challenges, and changes to all the nations of the world, Nigeria inclusive [1]. In a bid to contain the spread of this virus and to decrease the associated mortality and morbidity, a consensus of restricted movement, total lockdown in some places, have been reached in various countries. As a result of this, a country such as Nigeria which is heavily dependent on importation to meet its demands, will suffer a huge blow to several sectors including the pharmaceutical industry. Even though the local industry in Nigeria fairs better when compared to its counterparts in other developing countries in Sub-Saharan Africa [2], Nigeria is only able to meet 25% of its local demand. Nigeria’s pharmaceutical market predominantly runs on imports of active pharmaceutical ingredients machinery and quality control analytical equipment from abroad [2] . In Nigeria, over 70% of the prescribed medications are produced from active ingredients primarily sourced from firms in China and India [2]. Taking these into consideration alongside the travel restrictions in most countries, and the recently imposed travel ban on Nigerians, the current and future drug security in Nigeria is threatened. The added COVID-19 burden on the feeble healthcare system of Nigeria provides cause for grave concern. In an effort to manage the situation, the Central Bank of Nigeria has provided credit support as a palliative measure to reduce the impact of the pandemic on the health sector [3] . However, the availability of this fund to pharmaceutical industries is unknown. Lack of adequate infrastructures such as constant power supply, good water supply, functional transportation system and under-utilized manufacturing capacity have been some of the major challenges facing pharmaceutical industry in Nigeria [2]. Efforts should be made to address these challenges in order to reduce the total manufacturing and distribution costs. Adopting and enforcing production and distribution friendly policies amid and post-COVID-19 pandemic is essential. Community and hospital pharmacies have also been impacted as a result of the COVID-19 pandemic in Nigeria [4]. For instance, mode of operations has also evolved from face-to-face counselling into window-dispensing/counselling in hospital and community pharmacies. Low pharmacy workforce in the pre-COVID-19 era has also been previously reported. In a study carried out by Aniekan et al., in 2018 [5], there were 21,892 registered pharmacists in the country, of which only 59% are in active professional practice. It further stated that 42% of this licensed workforce are in community practice and 11% are hospital-based. A steady rise in number of migrating pharmacists have been observed thus bringing the pharmacists-patients ratio to about 1:14, 000 in 2018 which is way below the WHO recommendation of 1:2000. This remains worrisome in this COVID-19 era where the essential roles of pharmacists are much-needed. A large proportion of patients have stayed away from hospitals with the notion that health facilities increase their risk of contracting the virus. This has therefore resulted to a decline in the frequency of hospital visits which will negatively affect the provision of pharmaceutical care services including provision of point-of-care testing to patients. In lieu of hospitals treating COVID-19 patients, healthcare workers including pharmacists are constantly exposed to this highly infectious disease. This is a further concern since the lack of adequate personal protective equipment has been reported in Nigeria. Of great concern is that most community and hospital pharmacies are also not structured for effective physical distancing. In Nigeria, there is no guideline or standard operating procedure specific to the community and hospital pharmacies on COVID-19. Guidelines from international bodies or countries may not be applicable to Nigeria due to significant differences in pharmacy practice, demographics, and different COVID-19 transmission dynamics. There is a need for relevant tailor-made guidelines on how to handle COVID-19 in community and hospital pharmacies. Decline in patients’ hospital visits implies a higher flux of patients to community pharmacies for refills and as first points of contact for minor ailments. A large proportion of COVID-19 patients present with mild symptoms similar to a cold or flu and do not require hospitalization. Consultation with such patients put the community pharmacist at risk of contracting the virus. More than 30 frontline pharmacists across the country have tested positive for COVID-19 [6]. This situation suggests a possible increase in pressure on the available community pharmacy outlets in the country. Coupled with the reduced importation capacity which signifies impending drug scarcity, the surge to community pharmacies intensifies the pressure on the available stock of medicines which may result into price hikes and scarcity. COVID-19 presents an opportunity for increased production of drugs locally, while also relieving stock-out burden on available retail outlets. It is time to rethink pharmaceutical sector in Nigeria and ensure that health emergencies do not disrupt their much-needed roles in the health system.